If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15c+85=c
We move all terms to the left:
15c+85-(c)=0
We add all the numbers together, and all the variables
14c+85=0
We move all terms containing c to the left, all other terms to the right
14c=-85
c=-85/14
c=-6+1/14
| {11(y-10)}=(4y-5 | | 10-4×=3y | | 2/3=2x-7/3x+4 | | (x+19)=(5x-45) | | -6k=6-6k | | 180=(y+10)+2y | | 3m−2m=5 | | –10−2h=–3h | | 6(3x+1)=-102 | | 58=8+5n | | 13x+4=27x-2 | | 8-2(4x-3)=-26 | | 2(x+2)-2=4x-2(-3+x) | | 3.2=-0.4nn= | | 5(w+7)=-5(3w-4)+2w | | 3+6b=2b+3b | | −12(3x−4)=11 | | 2(x+2)-2=4x-2(-3+x | | 1233.99=172x+19.99 | | 17−3x+15=8x+30 | | X+(b)=30 | | 3900=4x+5x | | -5x-11=+64 | | 1233.99=127x+19.99 | | (x+5)=(3x-43) | | 4(3x-2)=6x-7+2x | | 17−3x+15=6x+30−2x | | 5+x+2x+10=30 | | 22=u-53 | | 4y2-13=y2+14 | | X(b)=30 | | 5/2x+18=8x |